Dampak Investasi Infrastruktur Di Sulawesi Selatan Terhadap Struktur Ekonomi Wilayah Di Indonesia - Enggar Paskhalis Lahu (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2021)
The government has carried out infrastructure development in various regions of Indonesia to encourage regional growth and address development inequalities. In Presidential Decree No. 48 In 2014, the Province of South Sulawesi (Sulsel), which is in the Eastern Region of Indonesia (KTI), received an infrastructure investment value of IDR 39.47 trillion consisting of 33 projects. This paper analyzes the impact of infrastructure investment in South Sulawesi using the IRIO 2015 table to see how much impact it has on output, added value, and income for South Sulawesi, other provinces in Sulawesi Island, the KTI region, and the West Region of Indonesia (KBI). From the results, it can be seen that the total impact of infrastructure development is mostly received by South Sulawesi itself, but the rest of the impact flows are more received by provinces in the KBI region than KTI. To increase the flow of impact to KTI areas, local governments must strengthen economic cooperation between regions in KTI areas so that the economic sector in other regions can be lifted